Towards Clinical Sustainability from Evolution to Revolution: A Study of Sustainable Factors for Law Clinics. (July 2019) - Nwedu, Cosmos Nike
Clinical legal education (CLE) has grown from country-specific concept to a widely feted global practice with a high degree of momentum and acceptability. There is an increasing profound interest from universities, law schools, law academics and researchers, non-governmental organizations and students alike towards mainstreaming this concept. A growing body of literature designed around different creativities, ideas and methodologies aimed at expanding its scope of operability, values and rationales has sufficed. Nonetheless, there is a little strand of academic literature on the sustainability of CLE in all respects. While the question of whether CLE has come to stay may seem axiomatic, it however depends on certain critical sustainable factors. Thus, it makes sense to consider in what ways law clinics can bring a sustained clinical legal practice. This article takes a forward-looking approach by exploring critical sustainable factors considered as crucial accelerators for wheeling clinical pedagogy in growth motion and driving the effectiveness of law clinics and clinical activities. The study provides a framework for ensuring not only that the rationalistic status quo of CLE is maintained but also offers a futuristic context in fostering clinical movement and activities and ensuring inclusiveness.